Trends of Rotavirus in Nepal - Pandey, B D; Pun, S B (Kathmandu University Medical Journal, 2012)
Background Rotavirus gastroenteritis is the major cause of morbidity and mortality in infants and young children worldwide. Safe and effective rotavirus vaccine is needed to have significant impact on severe rotavirus gastroenteritis. Currently, two live oral rotavirus vaccines have been licensed in many countries. Knowledge on distribution of human rotavirus of G and P types are essential before rotavirus vaccines are introduced in the target populations. Objective To observe the trends of rotavirus strains in children below five years of age, during the years, 2003-2005 in Nepal. Methods Stool specimen collected from children with acute diarrhea who were referred to observation unit or hospitalized in Kanti Children’s Hospital between 2003 and 2005 were examined. Meteorological data was obtained from Ministry of Environment, Nepal to examine the possibility on the impact of weather on rotavirus infection. Results Of 1250 stool specimens, 271(22%) were positive for rotavirus by Rotaclone ELISA. G1 was the most common serotype in the first year of study, and G2 in the following year. G12 serotype emerged and remained predominant in two consecutive years. In addition, G9 and G3 emerged in the second year of the study. Children less than three years of age were commonly affected. The records reveal that rotavirus infection is related to the climate, and is commonly seen in the dry season, peaking in January. Conclusions Continued surveillance of different regions is needed to monitor the trend of rotavirus strains and to establish rotavirus disease burden, which will help policy makers to make a decision in introducing rotavirus vaccine in Nepal. http://dx.doi.org/10.3126/kumj.v9i1.6259 Kathmandu Univ Med J 2011;9(1):32-35